DOES EARLY ACCESS TO PENSION WEALTH IMPROVE HEALTH?. (7th July 2020) - Kim, Seonghoon; Koh, Kanghyock
Abstract : We examine the health impacts of early access to public pension wealth by exploiting a unique policy in Singapore allowing individuals to withdraw a proportion of their pension savings after their 55th birthday. For the identification, we employ a regression discontinuity design by comparing individuals before and after their 55th birthday. To address anticipated and lagged health impacts, we adopt the donut regression discontinuity approach. Using nationally representative monthly panel data, we find that early access to pension wealth improves self‐reported overall health. ( JEL I10, H55, D15)